5x^2 = -2x + 3
Your first step would be to bring everything over to the left hand side. We want quadratics equated to 0.
5x^2 + 2x - 3 = 0
We now solve this using the quadratic formula. Remember that it goes
x = [-b +/- sqrt(b^2 - 4ac)] / [2a]
x = [-2 +/- sqrt(4 - 4(5)(-3)) / [10]
x = [-2 +/- sqrt(4 + 60)] / [10]
x = [-2 +/- sqrt(64)] / [10]
x = [-2 +/- 8]/10
Therefore, your two solutions are
x = [-2 + 8]/10 and [-2 - 8]/10
x = {6/10, -10/10}
x = {3/5, -1}
2007-01-08 07:57:29
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
In order to get something that you can work using the quadratic formula, you've gotta move some numbers around first.
Start by adding 2x to both sides.
5x^2 + 2x = 3
Subtract 3 from both sides. . .
5x^2 + 2x - 3 = 0
Look familiar?
Now all you have to do is plug the numbers into the formula (a = 5, b = 2, c = 3), and work it like you would any other problem.
2007-01-08 16:00:07
·
answer #2
·
answered by AskerOfQuestions 3
·
0⤊
0⤋
I assume that means 5x^2 = -2x +3
Step 1: write equation as 5x^2 +2x - 3 = 0
Step 2: remember quadratic formula which states that for
ax^2 + bx + c = 0 then x = (-b +/- sqrt(b^2 - 4ac))/2a
Step 3: plug in a = 5, b = 2, c = -3 from step 1 into the formula.
2007-01-08 15:59:44
·
answer #3
·
answered by quesotrain 1
·
0⤊
0⤋
You mean 5x^2 = -2x + 3, right?
5x^2 + 2x -3 = 0
ax^2 + bx -x = 0
Quadratic formula
x1 = (-b + squareroot(b^2 - 4ac))/2a
x2 = (-b - squareroot(b^2 - 4ac))/2a
x1 = 3/5
x2 = -1
2007-01-08 16:02:44
·
answer #4
·
answered by Cu Den 2
·
0⤊
0⤋
bnm
... 5x*2=-2x+3 =>
5x^2 + 2x - 3 = 0
factor this into:
(5x -3) (x +1) = 0
here, observe that either
5x - 3 = 0 ........or
x + 1 = 0
meaning that
x = 3/5 or
x = -1
2007-01-08 15:56:31
·
answer #5
·
answered by atheistforthebirthofjesus 6
·
0⤊
0⤋
5x^2 = -2x + 3
5x^2 +2x -3 = 0
quadratic formulat is x = (-b & sqrt(b^2-4ac))/(2a) where ax^2 + bx + c = 0 and & stands for the "plus or minus" sign (it isn't available directly on a keyboard).
sqrt(b^2-4ac) = sqrt(64) = 8
x = (-2 + sqrt(64)) / 10 = 0.6 or x = (-2 - sqrt(64)) / 10 = -1
2007-01-08 16:02:22
·
answer #6
·
answered by infinitys_7th 2
·
0⤊
0⤋
1. 5x² + 2x - 3 = 0
Use the quadratic formula.
The end.
2007-01-08 15:57:38
·
answer #7
·
answered by bequalming 5
·
0⤊
0⤋
Nm, the guy at the top who put a placeholder answer in then edited to say what I said is correct.
2007-01-08 15:57:50
·
answer #8
·
answered by Kevin C 3
·
0⤊
0⤋
........................../´¯....
.......................,/¯../....
....................../..../.....
.........../``/´¯/'...'/´¯¯`•Â¸
........../'/.../..../......./...
........('(...´...´.... ¯~/'...')
.........\.................'.....
..........''...\.......... _.•Â´
............\..............(
..............\.............\....
do your own homework
2007-01-08 16:00:29
·
answer #9
·
answered by Anonymous
·
0⤊
3⤋